2016
DOI: 10.1016/j.ajhg.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing the GRHL3 Coding Region Reveals Rare Truncating Mutations and a Common Susceptibility Variant for Nonsyndromic Cleft Palate

Abstract: Nonsyndromic cleft lip with/without cleft palate (nsCL/P) and nonsyndromic cleft palate only (nsCPO) are the most frequent subphenotypes of orofacial clefts. A common syndromic form of orofacial clefting is Van der Woude syndrome (VWS) where individuals have CL/P or CPO, often but not always associated with lower lip pits. Recently, ∼5% of VWS-affected individuals were identified with mutations in the grainy head-like 3 gene (GRHL3). To investigate GRHL3 in nonsyndromic clefting, we sequenced its coding region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 40 publications
4
103
0
2
Order By: Relevance
“…Our results, as well as previously published data including IRF6 ,20 42  MSX1 ,43  TBX22 44 and GRHL3 ,41 substantiate evidence for Mendelian transmission (with incomplete penetrance) of aetiological variants in ‘syndrome-causing genes’ in subclinical or non-syndromic cleft families. Therefore, custom-designed panels including CL/P-syndrome-causing genes should be used in diagnostic screens when a particular syndrome is suspected and also for families with nsCL/P.…”
Section: Discussionsupporting
confidence: 91%
“…Our results, as well as previously published data including IRF6 ,20 42  MSX1 ,43  TBX22 44 and GRHL3 ,41 substantiate evidence for Mendelian transmission (with incomplete penetrance) of aetiological variants in ‘syndrome-causing genes’ in subclinical or non-syndromic cleft families. Therefore, custom-designed panels including CL/P-syndrome-causing genes should be used in diagnostic screens when a particular syndrome is suspected and also for families with nsCL/P.…”
Section: Discussionsupporting
confidence: 91%
“…The first study, despite interrogating 400 CP case-parent trios, did not identify any statistically significant SNP main effects (Beaty et al 2011). The second study identified a single locus associated with CP, but this association signal was limited to European populations because of very low frequencies of the risk allele in other populations (Leslie et al 2016b; Mangold et al 2016). For both CL/P and CP, the identified risk loci only account for a modest portion of the genetic variance of OFCs, suggesting that additional genetic risk factors may be involved.…”
Section: Introductionmentioning
confidence: 99%
“…While these data confirm an important role of Grhl3 in the pathogenesis of NTDs in mouse models, its role in the human NTD pathology remained unclear (Ting et al., ). To date, variants in GRHL3 in humans have been associated only with a minority (5%) of cases presenting Van Der Woude syndrome 2 (VWS2; MIM# 606713) (the most common syndromic form of cleft lip and palate (Peyrard‐Janvid et al., ) and recently with nonsyndromic cleft palate (Leslie et al., ; Mangold et al., )).…”
Section: Introductionmentioning
confidence: 99%